1987
DOI: 10.1073/pnas.84.24.9035
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 enhancement of interleukin 3-dependent proliferation of multipotential hemopoietic progenitors.

Abstract: Interleukin-6 (IL-6, also known as B-cell stimulatory factor 2/interferon P2) was previously shown to support the proliferation of granulocyte/macrophage progenitors and indirectly support the formation of multilineage and blast cell colonies in cultures of spleen cells from normal mice. We report here that IL-3 and IL-6 act synergistically in support of the proliferation of murine multipotential progenitors in culture. The time course of total colony formation by spleen cells isolated from mice 4 days after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
252
0
5

Year Published

1995
1995
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 725 publications
(269 citation statements)
references
References 37 publications
12
252
0
5
Order By: Relevance
“…IL-6 supports HPC proliferation, 28,29,58,59 and we have recently shown it to be a critical regulator of PTH actions in HPC expansion. 13 Because the calvarial organ is composed primarily of stromal osteoblastic cells, the predominant PPR-expressing cell population in the bone marrow, the more significantly increased PTH-induced IL-6 mRNA in Prg4 mutant calvaria suggests that a stromal osteoblastic cell is the target of PTH actions to modulate IL-6 and hematopoietic cells in the marrow of Prg4 mutant mice.…”
Section: Discussionmentioning
confidence: 96%
“…IL-6 supports HPC proliferation, 28,29,58,59 and we have recently shown it to be a critical regulator of PTH actions in HPC expansion. 13 Because the calvarial organ is composed primarily of stromal osteoblastic cells, the predominant PPR-expressing cell population in the bone marrow, the more significantly increased PTH-induced IL-6 mRNA in Prg4 mutant calvaria suggests that a stromal osteoblastic cell is the target of PTH actions to modulate IL-6 and hematopoietic cells in the marrow of Prg4 mutant mice.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown that IL-6 and IL-11 can amplify the proliferation of immature hematopoietic cells when in combination with stem cell factor and other regulators (18,19). A similar action has been reported for LIF when acting on human cells (20) and LIF, and IL-6 have been reported to amplify the proliferation of purified murine progenitor cells when used in combination with IL-3, GM-CSF, M-CSF, or SCF (21).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as shown in Figure 3, patients with detectable serum IL-6 levels had significantly higher plasma fibrinogen levels (4.67 ± 0.65 g 1') than patients without detectable serum IL-6 levels (3.80 ± 0.38 g I-'; P <0.05) and patients with benign lung diseases (3.21 ± 0.70 g -l1; P<0.05). (Ikebuchi et al, 1987;Ishibashi et al, 1989), we studied the possible correlation between serum IL-6 concentrations and blood platelet counts. As shown in Figure 4, there was no significant difference in blood platelet counts between lung cancer patients with detectable (26.5 ± 0.51 x 104 il-1) or undetectable (26.1 ± 0.20 x 104ylh 1) serum IL-6 levels or patients with benign lung diseases (30.1 ± 0.33 x 104 ll-1).…”
Section: Correspondence: H Yanagawamentioning
confidence: 99%